(untitled) (Bioscience Journal, 2015)
The present study aimed to investigate the foraging dynamic of an ant community in an urban semideciduous mesophitic forest. A total of 4,297 individuals, distributed in 23 species, seven genera and four subfamilies were sampled in January, April, July and October of 2010. Four ant species guilds were found: leaf cutters, soil-dominant omnivores, soil and vegetation opportunists and large-sized epigaeic predators. There were no significant differences in total of species richness and abundance of individuals in samples among the months evaluated. However, there was a clear substitution (turnover) of species over the months. Nine species were sampled exclusively in the rainy period and five species were present only during the dry period. Thus, the species turnover over the months support the hypothesis that ant communities present a temporal dynamics in their foraging activities even in an urban forest fragment. In general, the abundance of ants foraging on soil was greatest during the months with greater rainfall. However, two species belonging to the guild of opportunistic ants from soil and vegetation doubled the number of foraging individuals in period during the months with less precipitation. These findings support that ant communities, independent of isolation and environment (urban or natural), have temporal dynamics that arise from factors relating to the biology and behavior of the group.